2009
DOI: 10.1080/01421590802337104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating training for a simulated team in complex whole procedure simulations in the endovascular suite

Abstract: Introduction: Simulators supporting the development of technical skills for complex procedures are gaining prominence. Safe performance of complex procedures requires effective team interactions. Our research group creates 'whole' procedure simulations to produce the psychological fidelity of clinical settings. Recruitment of real interventional team (IT) members has proved challenging. Actors as a simulated team are expensive. We hypothesised that medical students and trainees in a vascular unit could authent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The second breakdown was not in the new system but in the knowledge base of the individual responding to the crisis. This breakdown highlights the importance of standardised team training, both for simulated teams and in real life—a concept which been elaborated on by Nestel et al ,15 who described the use of medical students and trainees in a vascular unit to portray members of a simulated endovascular suite for carotid stenting and reported that a simulated interventional team proved feasible with these resources, and that authentic psychological fidelity complemented the physical fidelity of the simulated suite. While the test subject nurse did react and call for assistance, the confederate playing the role of the anaesthesiologist did not identify the problem in a timely manner leading to the adverse event occurring.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The second breakdown was not in the new system but in the knowledge base of the individual responding to the crisis. This breakdown highlights the importance of standardised team training, both for simulated teams and in real life—a concept which been elaborated on by Nestel et al ,15 who described the use of medical students and trainees in a vascular unit to portray members of a simulated endovascular suite for carotid stenting and reported that a simulated interventional team proved feasible with these resources, and that authentic psychological fidelity complemented the physical fidelity of the simulated suite. While the test subject nurse did react and call for assistance, the confederate playing the role of the anaesthesiologist did not identify the problem in a timely manner leading to the adverse event occurring.…”
Section: Discussionmentioning
confidence: 88%
“…Patient actors were medical students who volunteered their time and were trained with a standardised script during a training session held prior to the simulated exercise. Similar to the work described by Nestel et al ,15 the standardised trained students as patient actors in these simulated exercises served to preserve the fidelity of the scenario.…”
Section: Methodsmentioning
confidence: 99%
“…18 In comparison to open surgery, endovascular skills are particularly suited to this since stent graft planning, use of imaging workstations, ultrasound skills, and catheter skills do not have to be practised in the operating theater. There is evidence that clinically relevant outcomes can be improved through cognitive training and complex simulation for endovascular procedures, 19 21 and competence assessment in vascular surgery can also be reliably performed in the simulated environment. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…This includes mentored training in patients within an interventional apprenticeship, a process that is unlikely to ever be entirely replaced by simulation [41]. Indeed, simulation is not a substitute for curriculum-based training, or for participating in the actual care of real patients -it should be used in support of both [34][35][36][37][38][39][40][41][42].…”
Section: What This Means For Ir Now and In The Futurementioning
confidence: 99%
“…Focusing on known strengths, such as training procedural sequencing, cognitive and communication skills, gross motor behaviours and teamwork within context, represent opportunities to use simulation as a component of a recognised IR curriculum [30,[34][35][36].…”
Section: Commentary: Using Simulation For Interventional Radiology Trmentioning
confidence: 99%